Customary Law and Agrarian Conflict:Analysis of Land Dispute Resolution Based on Local Wisdom - Basri Basri (Journal of Adat Recht, 2026)
Agrarian conflict is a recurring structural problem in Indonesia, particularly in areas inhabited by indigenous communities. The tension between state law and customary law is often the primary source of protracted land disputes. This study analyzes how land dispute resolution mechanisms based on local wisdom, derived from customary law, can function effectively as an alternative or complement to the formal justice system. Using normative legal research methods supported by sociological and historical approaches, this study examines various customary law instruments, jurisprudence, and field studies on land dispute resolution practices in indigenous communities across Indonesia. The results indicate that customary deliberation mechanisms, customary elder institutions, and communal consensus values ​​embodied in local wisdom are highly effective in achieving just and sustainable dispute resolution. However, the weak legal recognition of customary institutions and decisions is a major obstacle to their implementation. This study recommends strengthening the national legal framework that integrates customary mechanisms into the agrarian dispute resolution system, accompanied by empowerment of local customary institutions.